Pengaruh Profitabilitas dan Nilai Perusahaan Terhadap Harga Saham pada Perusahaan Sektor Pertambangan - Muhamad Irgi Fahreji Mokoagow; Herlina Rasjid; Selvi (Masyarakat Ekonomi Syariah Bogor, 2025)
The study aimed to discover how profitability and firm value affect stock princes based on a case study on mining sector companies listed on the Indonesia Stock Exchange in 2020-2023. The rasios used in the company’s financial statements are profitability and the firm value in the form of Return Of Asset And Tobin’s Q. The results of this report become a guidebook for investors in assessing the company and affecting the company’s stock price. This study used a quantitative approach with multiple linear regression analysis methods. The sampling technique in this study used purposive sampling with a population of 24 companies and 96 data on mining sector companies thet meet the criteria as a sample. The data colletion technique in this study used secondary data from financial statements published by mining sector companies listed on the Indonesia Stock Exchange (IDX). Based on partial analysis, profitability has a positive and significant effect on the stock price, and the firm value has a positive and significant effect on the stock price. Simultaneously, profitability and firm value affect stock price.